2021
DOI: 10.1002/npr2.12174
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated long‐term forgetting is a BACE1 inhibitor‐reversible incipient cognitive phenotype in Alzheimer’s disease model mice

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
(60 reference statements)
1
7
0
Order By: Relevance
“…More recently and in line with previous research, Ohno (2021) has provided experimental evidence of ALF as a sensitive measure of memory for assessing the effects of antiamyloid treatment in young (4-month-old) AD transgenic mice. While untreated control mice were able to form and initially retain contextual fear memories but lost these memories at an accelerated rate over 28 days, mice pretreated with a β-secretase inhibitor showed almost complete normalization of their long-term forgetting rate.…”
Section: The Phenomenon Of Alfsupporting
confidence: 68%
See 1 more Smart Citation
“…More recently and in line with previous research, Ohno (2021) has provided experimental evidence of ALF as a sensitive measure of memory for assessing the effects of antiamyloid treatment in young (4-month-old) AD transgenic mice. While untreated control mice were able to form and initially retain contextual fear memories but lost these memories at an accelerated rate over 28 days, mice pretreated with a β-secretase inhibitor showed almost complete normalization of their long-term forgetting rate.…”
Section: The Phenomenon Of Alfsupporting
confidence: 68%
“…While untreated control mice were able to form and initially retain contextual fear memories but lost these memories at an accelerated rate over 28 days, mice pretreated with a β-secretase inhibitor showed almost complete normalization of their long-term forgetting rate. Although trials of β-secretase inhibitors in humans have not yet shown clinical efficacy in AD (Hampel et al, 2021; Ohno, 2021), the results of the animal research reinforce the idea that intervening at earlier disease stages, and using more sensitive cognitive measures such as ALF, may be necessary to observe behavioral effects.…”
Section: The Phenomenon Of Alfmentioning
confidence: 89%
“…AD is also described by the gradual formation of insoluble amyloid plaques and the deposition of amyloid beta-peptide in the brain [27]. Beta-site amyloid precursor protein cleaving enzyme 1 (BACE1) is a potent drug target for the treatment of AD as prolonged inhibition of BACE1 restricts the structural and functional synaptic plasticity in rats (altering the metabolism of BACE1 substrates) [28,29]. The memory-boosting action of E. prostrata is also supported by its BACE 1 inhibiting property.…”
Section: Discussionmentioning
confidence: 99%
“…A low concentration of occludin may cause the BBB to be more permeable [73], causing the upregulation of BACE1 enzymes in the brain. BACE1, in turn, may activate several underlying mediators that result in neuronal apoptosis and memory impairments [74]. Along with this, TNF-α is associated with hippocampal-dependent memory in the brain.…”
Section: The Interplay Between Obesity Oxidative Stress Inflammation ...mentioning
confidence: 99%